Multicenter retrospective study of initial treatment outcome and feasibility of initiating dose reduction of cabozantinib in unresectable hepatocellular carcinoma. Issue 2 (18th October 2022) - Tomonari, Tetsu; Tani, Joji; Ogawa, Chikara; Deguchi, Akihiro; Senoh, Tomonori; Moriya, Akio; Shibata, Hiroshi; Fukuno, Hiroshi; Tanaka, Hironori; Tanaka, Takahiro; Taniguchi, Tatsuya; Sogabe, Masahiro; et al.
Abstract: Aim: Cabozantinib (CAB), a multiple kinase inhibitor, has been approved for use in patients with previously treated unresectable hepatocellular carcinoma (uHCC). However, real‐world clinical data are lacking, particularly clinical data regarding dose modifications of CAB. We analyzed the clinical outcomes of CAB in uHCC and compared treatment outcomes between the full‐ and reduced‐dose groups. Methods: This multicenter, observational study included patients with uHCC who were treated with CAB from March 2021 to April 2022. Patient characteristics, efficacy, and safety were compared between the full‐ and reduced‐dose groups. Results: Twenty‐six patients from eight institutes were analyzed. Cabozantinib was administered as a third‐line or later treatment in 25 (96.2%) patients and postimmunotherapy in 21 (80.5%) patients. There were 15 patients in the full‐dose group (60 mg CAB) and 11 in the reduced‐dose group (40 or 20 mg CAB). The objective response rate (ORR) and disease control rate (DCR) were not significantly different between the two groups. The ORR was 6.7% for the full‐dose group and 9.1% for the reduced‐dose group, and the DCR was 53.4% and 81.8%, respectively. Progression‐free survival analysis showed no significant differences between the two groups. The incidence of decreased appetite, fatigue, and diarrhea, and the rate of discontinuation and dose reduction, was significantly higher in the full‐dose group. Conclusions: Our study suggests that the efficacy and safety of CAB in real‐world clinical practice are comparable to those of the phase III trial (CELESTIAL), and that dose reduction of CAB may be a safer treatment option.